Indigenous Social Work Approaches to Strengthen Self-Motivation of Children in Conflict with the Law in Social Rehabilitation at UPTD Griya Bina Karsa Bogor Regency West Java - Wirawan, Zaka; Ismudiyati, Yuti Sri; Huripah, Enung (SAMPURASUN, 2025)
Children in conflict with the law (CICL) often experience moderate levels of self-motivation when undergoing social rehabilitation. This study examines self-motivation using the Intrinsic Motivation Inventory, which consists of seven dimensions: Interest/Enjoyment, Perceive Competence, Effort/Usefulness, Pressure/Tension, Perceived Choice, Value/Usefulness and Relatedness with Counsellor. This study aims to explore how indigenous social work approaches rooted in Sundanese cultural values silih asih, silih asah, silih asuh (mutual love, mutual learning, and mutual guidance) can contribute to strengthening self-motivation among CICL. Using a quantitative descriptive method with 37 respondents at UPTD Griya Bina Karsa, West Java. The findings reveal that 75.68% of participants demonstrate a moderate level of self-motivation. The moderate scores were found in the aspects of perceived choice (78.38%), pressure/tension (72.97%), and connectedness with mentors (81.08%). These results highlight the importance of integrating local cultural values into rehabilitation practices. By embedding indigenous social work principles, rehabilitation programs can reduce psychological tension, foster stronger relationships between children and mentors, and encourage autonomy in decision-making. Such an approach not only improves individual motivation but also reaffirms cultural heritage as a source of resilience and social transformation.